Understanding Student Personality Types According To Hippocrates Galenus Theory - Rimulawati, Vegestina; Harahap, Nur Hasanah; Eliza, Riana; Afdhol, Rahmi Syarima (International Research-Based Education Journal, 2024)
This writing uses the literature search method by twenty-one electronic databases, namely Google Scholar and Google Book. Research from journals published between 2009-2022. Understanding students' personality types can help identify in solving student problems because each student has its own personality. This writing aims to know and understand students' personalities based on the Hippocrates-Galenus theory. By knowing the characteristics and personality types of each student, individual planning is carried out to help students solve problems.